Methodology for managing energy development of production facilities in the gas industry - Anatolii A. Shapovalo (Записки Горного института)
The current stage of Russia's development is characterized by dynamic changes in the operating conditions of gas industry enterprises, which leads, among other things, to significant adjustments in approaches to the development of energy production facilities. The article examines on the system level the ways to improve energy supply, taking into account the goals and objectives of the development of production facilities from the conditions of solving a single technological problem of the gas industry – high-quality gas supply to consumers. The optimal functioning of energy supply systems, taking into account the peculiarities of technological processes at production facilities, presupposes the development models coordination of production facilities energy complexes with the gas industry enterprises parameters based on an integrated unified information space at all stages of their life cycle. The structure of production facility energy complex and the connections of its elements with related systems are justified taking into account the purposes of their creation and the requirements for production facilities. Problem solving for each system element as well as the exchange of information between equivalent systems is done on the basis of a developed hierarchy of optimization problems adjusted depending on the type of tasks of energy supply improvement of a production facility. Determining the values of parameters and indicators of energy complexes, as well as optimizing the lists and content of work to improve the energy supply of production facilities, is planned to be carried out in accordance with the methodology under consideration using a set of mathematical models.